Spatial impact of the built environment on street vitality: A case study of the Tianhe District, Guangzhou - Wangbao, Liu (Frontiers in Environmental Science, 2022)
Taking the Tianhe District in Guangzhou, China, as a case and the urban street (road) as the basic research unit, this study analyzes the relationship between the built environment and street vitality to analyze the influencing factors of street vitality. The Tencent location service data are used to characterize street vitality, and the OLS and GWR models are used to construct the statistical relationship between the built environment and street vitality after establishing the urban built environment index. The results show that spatial heterogeneity is considered in the GWR model based on local geographic weighting, and its fitting effect is better than that of the OLS model, which can reveal the micro-local characteristics of the built environment’s effect on street vitality. Increasing the land-use mixing degree, new and old building mixing degrees, and land-use intensity (building density and volume ratio) can significantly increase street vitality, which proves to a certain extent that Jacobs’s relevant discussion is still highly practical for the Tianhe District.